2021
DOI: 10.1155/2021/5585884
|View full text |Cite
|
Sign up to set email alerts
|

Identification of MicroRNAs in Taxillus chinensis (DC.) Danser Seeds under Cold Stress

Abstract: Taxillus chinensis (DC.) Danser, a parasitic plant that belongs to the Loranthaceae family, has a long history of being used in the Chinese medicine. We observed that the loranthus seeds were sensitive to temperature and could lose viability below 0°C quickly. Thus, we performed small RNA sequencing to study the microRNA (miRNA) regulation in the loranthus seeds under cold stress. In total, we identified 600 miRNAs, for the first time, in the loranthus seeds under cold stress. Then, we detected 224, 229, and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Mistletoe was later discovered for its miraculous effects, and traditional medicine spread it over time to many parts of the world, in particular, V. album L. and Loranthus (Taxillus Chinensis (DC.) Danser) [28,29]. The latter belongs to the family Loranthaceae, distributed mainly in southern and southwestern China, is known as "Sang Ji Sheng", and its leaves and stems have a long history in traditional Chinese medicine, is used to treat rheumatism, arrhythmia, angina pectoris, hypertension, stroke [28].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mistletoe was later discovered for its miraculous effects, and traditional medicine spread it over time to many parts of the world, in particular, V. album L. and Loranthus (Taxillus Chinensis (DC.) Danser) [28,29]. The latter belongs to the family Loranthaceae, distributed mainly in southern and southwestern China, is known as "Sang Ji Sheng", and its leaves and stems have a long history in traditional Chinese medicine, is used to treat rheumatism, arrhythmia, angina pectoris, hypertension, stroke [28].…”
Section: Methodsmentioning
confidence: 99%
“…Danser) [28,29]. The latter belongs to the family Loranthaceae, distributed mainly in southern and southwestern China, is known as "Sang Ji Sheng", and its leaves and stems have a long history in traditional Chinese medicine, is used to treat rheumatism, arrhythmia, angina pectoris, hypertension, stroke [28]. V. album L. also has a long traditional history of about 100 years, used in German-speaking countries in cancer treatment therapy [29].…”
Section: Methodsmentioning
confidence: 99%
“…For the cold treatment experiment, we selected 300 T. chinensis seeds with similar appearances, including sizes, weights, and health conditions. We observed that the T. chinensis seeds were sensitive to temperature and that 0°C was a suitable temperature to study the cold-responsive genes [ 23 ]. The seeds were divided into three groups—no treatment (A0) and cold treatment for 12 h (A1), 24 h (A2), and 36 h (A3).…”
Section: Methodsmentioning
confidence: 99%
“…Previously, our lab identified genes that are expressed in response to water loss in T. chinensis seeds [ 22 ], such as RD22, HSP, and various TFs (MYB, WRKY, and ethylene-responsive transcription factors), and reported the regulatory miRNAs in T. chinensis seeds in response to cold [ 23 ], such as miR408, miR393b, miR946, ath-miR779.2, miR398, and miR9662. Interestingly, ICE3, IAA13, and multiple TFs (e.g., WRKY and CRF4 and TCP4) were shown to be targets of the dysregulated miRNAs identified in the T. chinensis seeds under cold stress [ 23 ]. In the present study, we used the same material as the miRNA study and investigated changes in gene expression changes in T. chinensis seeds in response to cold using transcriptome sequencing technology.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, T. chinensis can only be propagated by seed, and its seed is generally recalcitrant, exhibiting sensitivities to both dehydration and low temperature ( Pan et al 2021 ), which ultimately hinder the species’ utilization. Previous transcriptomic and proteomic studies have investigated the molecular mechanisms associated with the dehydration tolerance of T. chinensis ( Wei et al 2017 ; Pan et al 2021 ), and cold stress-related differentially expressed microRNAs (miRNAs) have also been reported ( Fu et al 2021 ). However, despite the insight these studies have provided into the recalcitrance, the whole-genome sequence of T. chinensis is still needed to fully understand the molecular mechanisms involved in the species’ seed recalcitrance.…”
Section: Introductionmentioning
confidence: 99%